Patient-reported outcomes with neoadjuvant vs adjuvant systemic therapy for operable breast cancer. (August 2019) - Zdenkowski, Nicholas; Butow, Phyllis; Spillane, Andrew; Douglas, Charles; Snook, Kylie; Jones, Mark; Oldmeadow, Christopher; Fewster, Sheryl; Beckmore, Corinna; Boyle, Frances M.
Abstract: Background: Neoadjuvant systemic therapy (NAST) is used for large operable or highly proliferative breast cancers. It is not known whether psychological outcomes differ according to the treatment sequence (chemotherapy or surgery first) or tumour response. Methods: This was a planned analysis of a multi-institutional single arm longitudinal study of patients considering NAST for operable breast cancer. Participants completed patient reported outcome questionnaires before and after the decision about NAST, between chemotherapy and surgery, and 12 months after diagnosis. Results: Fifty-nine women enrolled. Fourteen of 51 (28%) who received NAST experienced pathological complete response (pCR). Patients who had surgery first (n = 7) had higher baseline anxiety, and a greater decrease in anxiety at 12 months follow up, compared with patients who received NAST (n = 50) (a decrease from baseline of 34 pts vs 17 points; p = 0.033). Distress declined at a similar rate in surgery first and NAST groups. Mean satisfaction with decision score post-decision was significantly lower in the adjuvant group compared with NAST (22 vs 26, p = 0.02). No differences were seen between patients with pCR vs residual cancer in: distress, anxiety, satisfaction with decision, fear of progression, and decision regret. Conclusion: Most patients in this study proceeded with NAST when their surgeon offered it as an option. This exploratory analysis suggests that patients who chose surgery first tended to be more anxious, and had lower satisfaction with their decision, than those who had NAST. In patients who had NAST, lack of pCR does not appear to correlate with adverse psychological outcomes. Highlights: Psychological outcomes from neoadjuvant therapy for breast cancer are unknown. We questioned 59 women about anxiety, distress, and fear of progression or recurrence. Outcomes were compared according to response to chemotherapy and scheduling. Anxiety and distress declined over time. Fear of progression or recurrence were no different in responders or non-responders.